Fast current-driven domain walls and small skyrmions in a compensated ferrimagnet. Issue 12 (December 2018) - Caretta, Lucas; Mann, Maxwell; Büttner, Felix; Ueda, Kohei; Pfau, Bastian; Günther, Christian; Hessing, Piet; Churikova, Alexandra; Klose, Christopher; Schneider, Michael; Engel, Dieter; Marcus, Colin; et al.
Abstract Spintronics is a research field that aims to understand and control spins on the nanoscale and should enable next-generation data storage and manipulation. One technological and scientific key challenge is to stabilize small spin textures and to move them efficiently with high velocities. For a long time, research focused on ferromagnetic materials, but ferromagnets show fundamental limits for speed and size. Here, we circumvent these limits using compensated ferrimagnets. Using ferrimagnetic Pt/Gd44 Co56 /TaOx films with a sizeable Dzyaloshinskii–Moriya interaction, we realize a current-driven domain wall motion with a speed of 1.3 km s–1 near the angular momentum compensation temperature (T A ) and room-temperature-stable skyrmions with minimum diameters close to 10 nm near the magnetic compensation temperature (T M ). Both the size and dynamics of the ferrimagnet are in excellent agreement with a simplified effective ferromagnet theory. Our work shows that high-speed, high-density spintronics devices based on current-driven spin textures can be realized using materials in whichT A andT M are close together. Ferrimagnetic Gd44 Co56 near the compensation temperature enables domain wall motion with a speed of 1.3 km s–1 and room temperature skyrmions with diameters close to 10 nm.